Understanding Māori youth smoking : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Psychology at Massey University - Nepe, Melanie (Massey University, 2007)
The understanding of Māori youth smoking from a qualitative perspective has been neglected in the literature. While there has been a wide scope of research detailing the promoting and protective factors that put Māori youth at risk to smoking, there continues to be a high rate of smoking for Māori youth, particularly among young Māori females. This research endeavoured to discover what smoking means to Māori youth, and to explore the relationship between Māori youth smoking, and the effect that culture plays in the development of smoking behaviour. An objective of this research was to gather data that can inform and contribute to existing knowledge about Māori youth smoking, for the development of youth tobacco interventions. A qualitative study using focus groups was conducted to explore the meaning of smoking to Māori youth. The youth were aged 15-18 years of age. The focus groups explored the roles and meanings of smoking in Māori youth lives, by exploring their smoking histories, and maintenance processes involved in their daily experiences of smoking. Findings showed the initiation of smoking was strongly related to peer group membership. Role modeling by family and peers influenced smoking, with the progression of smoking linked to smoking etiquette and transition to adulthood. Maintenance of smoking was related to emotional well being and the normalization of smoking behaviour. Tobacco use was regarded as an important and enjoyable aspect of many of the participants' lives.
Keywords: Tobacco use; Youth, Maori; Hauora